S100a8/A9 proteins: critical regulators of inflammation in cardiovascular diseases - Sun, Yu; Xu, Han; Gao, Weihan; Deng, Jinlan; Song, Xiayinan; Li, Jie; Liu, Xijian (Frontiers in Cardiovascular Medicine, 2024)
Neutrophil hyperexpression is recognized as a key prognostic factor for inflammation and is closely related to the emergence of a wide range of cardiovascular disorders. In recent years, S100 calcium binding protein A8/A9 (S100A8/A9) derived from neutrophils has attracted increasing attention as an important warning protein for cardiovascular disease. This article evaluates the utility of S100A8/A9 protein as a biomarker and therapeutic target for diagnosing cardiovascular diseases, considering its structural features, fundamental biological properties, and its multifaceted influence on cardiovascular conditions including atherosclerosis, myocardial infarction, myocardial ischemia/reperfusion injury, and heart failure.